2014
DOI: 10.4161/viru.28776
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter ureolyticus

Abstract: Herein, we provide a brief overview of the emerging bacterial pathogen Campylobacter ureolyticus. We describe the identification of the pathogen by molecular as opposed to classical culture based diagnostics and discuss candidate reservoirs of infection. We also review the available genomic data, outlining some of the major virulence factors, and discuss how these mechanisms likely contribute to pathogenesis of the organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 97 publications
(176 reference statements)
2
27
0
Order By: Relevance
“…In Bullman's study (2011a), 23.8% of Campylobacter-positive diarrhea samples were identified as C. ureolyticus, pointing to the potential role of these bacteria as an important enteric pathogen. This implication was confirmed by their further studies on C. ureolyticus pathogenicity and growth control imposed on the species present in the intestine (O'Donovan et al, 2014). Other studies indicated that this emerging pathogen can cause a gastrointestinal illness via destruction of cell structures (Garmory and Titball, 2004), relocating across the cell using various proteins such as zona occludens toxin (Zot) and secreted fibronectin-binding proteins (CadF and FlpA) (Bullman et al, 2013), or forming biofilms (Burgos-Portugal et al, 2012).…”
Section: Gastroenteritismentioning
confidence: 86%
See 1 more Smart Citation
“…In Bullman's study (2011a), 23.8% of Campylobacter-positive diarrhea samples were identified as C. ureolyticus, pointing to the potential role of these bacteria as an important enteric pathogen. This implication was confirmed by their further studies on C. ureolyticus pathogenicity and growth control imposed on the species present in the intestine (O'Donovan et al, 2014). Other studies indicated that this emerging pathogen can cause a gastrointestinal illness via destruction of cell structures (Garmory and Titball, 2004), relocating across the cell using various proteins such as zona occludens toxin (Zot) and secreted fibronectin-binding proteins (CadF and FlpA) (Bullman et al, 2013), or forming biofilms (Burgos-Portugal et al, 2012).…”
Section: Gastroenteritismentioning
confidence: 86%
“…ureolyticus is another emerging gastrointestinal pathogen (O'Donovan et al, 2014), which is also found in human oral abscesses (Man, 2011). In Bullman's study (2011a), 23.8% of Campylobacter-positive diarrhea samples were identified as C. ureolyticus, pointing to the potential role of these bacteria as an important enteric pathogen.…”
Section: Gastroenteritismentioning
confidence: 98%
“…This represents the first report of C. ureolyticus in the faeces of patients presenting with gastroenteritis, suggesting a heretofore unreported role for this organism as an enteric pathogen. [72][73][74] Indeed, we showed that C. ureolyticus is second only to C. jejuni as the most common cause of Campylobacter associated gastroenteritis in Southern Ireland. 75 Furthermore, we reported a prominent seasonal distribution for campylobacteriosis (Spring), with C. ureolyticus (March) preceding C. jejuni/C.…”
Section: Bacterial Diagnosticsmentioning
confidence: 87%
“…An association with gastroenteritis has been shown for a broad range of species, including C. concisus [43], C. upsaliensis [44], C. fetus [45], C. ureolyticus [46], and C. hyointestinalis [47]. Lastovica and colleagues have shown that using non-selective culture, C. concisus and C. upsaliensis can be isolated with a frequency close to that of C. jejuni from diarrheal stools from children in South Africa, together representing 47% of all Campylobacter detections [48].…”
Section: Introductionmentioning
confidence: 99%